2015
DOI: 10.1002/ejp.682
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization stress sensitizes rat dorsal horn neurons having input from the low back

Abstract: Background: Stress is known to promote several forms of muscle pain including non-specific low back pain. However, the question if stress alone activates nociceptive central neurons has not been studied systematically. Here, we investigated the influence of repeated immobilization stress on dorsal horn neurons and behaviour in the rat. Methods: The stress consisted of immobilization in a narrow tube for 1 h on 12 days. Single dorsal horn neurons were recorded with microelectrodes introduced into the spinal seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
2
27
1
Order By: Relevance
“…The finding that in contrast to the deep input, the input from the skin was not affected by the swimming exercise, repeats own results obtained in previous experiments (Hoheisel et al., ). Simultaneously, the finding supports our assumption that the cutaneous afferents have very rigid and effective synaptic connections with dorsal horn neurons.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The finding that in contrast to the deep input, the input from the skin was not affected by the swimming exercise, repeats own results obtained in previous experiments (Hoheisel et al., ). Simultaneously, the finding supports our assumption that the cutaneous afferents have very rigid and effective synaptic connections with dorsal horn neurons.…”
Section: Discussionsupporting
confidence: 89%
“… The animals did not show any signs of distress (struggling, fighting and vocalisation) when they were put into the water‐filled cylinder. The marked hyperalgesia measured as PPT 2 days after the first NGF injection and after two bouts of swimming demonstrates the absence of strong stress‐induced analgesia. The proportion of neurons exhibiting new input from deep tissues decreased in our swimming experiments while – in contrast – the proportion of neurons increased in a previous study in which the effects of immobilisation stress was studied (Hoheisel et al., ). Likewise, the proportion of neurons having resting activity and the mean frequency of the resting activity decreased after swimming while in the study on rats deliberately stressed by immobilisation the proportion significantly increased (Hoheisel et al., ). This speaks strongly against a stress‐induced analgesia in the present study. …”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…More precisely, early life social stressors such as emotional abuse are associated with enhanced temporal summation of pain and enhanced touch sensitivity ( 109 ). Recent animal experiments indicate that stress itself is able to sensitize nociceptive neurons in the spinal cord ( 113 115 ) and that altered neuronal responses are accompanied by comparable changes in pain-related behavior. Schneider et al ( 115 ) for example have developed a new animal model on social rejection that mimicks ACE and found that social rejection produces long-lasting effects in pain sensitivity and social behavior that persist into adulthood ( 115 , 116 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these dorsal horn neurons behave as if sensitized during deep somatic inflammation. Interestingly, the rate of resting activity in the dorsal horn neurons of chronically stressed rats was considerably higher than in rats with chronically sensitized muscle nociceptors generated by complete Freund′s adjuvant or nerve growth factor (see references in Hoheisel et al., ). Surprisingly, the pain pressure threshold of the low back did not change in the chronically stressed rats, yet they showed signs of increased anxiety in the open field test.…”
mentioning
confidence: 99%